Psycho-emotional well-being and sexual function of patients with borderline ovarian tumors - A. Yu. Vlasina; A. G. Solopova; E. A. Son; A. E. Ivanov; I. M. Zhalyalova (Акушерство, гинекология и репродукция)
Aim: to study the severity of surgical menopause (postovariectomy syndrome), anxiety, depression and sexual function in patients with borderline ovarian tumors (BOTs) after radical treatment, depending on management in the rehabilitation period.Materials and Methods. There were examined 62 women of reproductive age (42.0 ± 4.1 years) after radical treatment of BOTs: Group I - 29 patients were observed during rehabilitation period according to the standards and the National Clinical Guidelines and underwent a 12-month Comprehensive Personalized Rehabilitation Program; Group II - 33 non-participating rehabilitation program patients. The Modified Menopausal Index (MMI) and all related constituent subscales, the level of anxiety and depression according to the HADS (Hospital Anxiety and Depression Scale), as well as sexual function according to the FSFI (Female Sexual Function Index) scale were assessed prior to surgery as well as 1, 6, and 12 months afterwards.Results. All study participants noted significantly aggravated symptoms related to surgical menopause as early as 1 month after treatment: the total MMI increased from 10.9 ± 2.2 score (lacked manifestations of surgical menopause) up to 37.0 ± 6.3 score (moderate manifestations) in Group I and from 10.5 ± 2.0 score (lacked manifestations of surgical menopause) up to 35.8 ± 4.3 score (moderate manifestations) in Group II. By the 12 months, MMI decreased down to 22.2 ± 4.6 score (mild manifestations) in Group I and remained almost unchanged in Group II - 36.9 ± 8.0 (moderate manifestations). In 93.1 % and 81.8 % women from Group I and Group II, respectively, 1 month after antitumor therapy, disorders of the psycho-emotional sphere were observed. In Group I, after 12 months parameters returned to preoperative baseline magnitude, whereas in Group II 87.9 % of patients noted their significant altered values. A twofold decrease in anxiety values according to the HADS was observed in Group I after 12 months of rehabilitation therapy, whereas in Group II, it was also decreased, but to a lower degree. While assessing level of depression, it was found to gradually increase in Group II within the first year after the operation, whereas in Group I it was steadily decreased. Within 1 month after radical treatment of BOTs, a significant decrease in sexual function and the FSFI index was observed in all women of reproductive age (from 23.7 ± 5.5 to 4.0 ± 1.2 score in Group I and from 23.4 ± 5.3 up to 4.0 ± 1.3 score in Group II). After 12 months of comprehensive rehabilitation, sexual function was almost completely recovered in Group I (22.5 ± 5.4 score), whereas in Group II sexual dysfunction was markedly evident (14.9 ± 6.4 score).Conclusion. Comprehensive personalized rehabilitation can reduce the negative symptoms of surgical menopause, normalize the psycho-emotional state, increase sexual function, and hence, improve the quality of life of patients with BOTs of reproductive age after radical treatment.